Philippine Economic Update, October 2016 : Outperforming the Region and Managing the Transition - World Bank (World Bank, Washington, DC, 2016)
The Philippines has emerged as one of the most dynamic economies in the East Asia region. Despite a challenging global economic environment, the Philippine economy has grown at a rapid pace over the past five years, supported by sound macroeconomic fundamentals and a highly competitive workforce. Strong capital investment and robust domestic demand have helped secure the Philippines’ position as the leading growth performer among major economies in East Asia and the Pacific. Public spending rose by more than 10 percent during the first half of 2016, as the government continued to implement its ambitious investment program. Services and industry remained the primary engines of growth, while the lingering effects of El Niño further diminished agricultural output and a weaker-than-expected global recovery continued to hinder the export sector. Nevertheless, the GDP growth rate rose from 5.5 percent in the first half of 2015 to 6.9 percent in the first half of 2016, enabling the Philippines to outperform regional peers such as China, Indonesia, Malaysia, Thailand, and Vietnam.